(untitled) (Transport systems and technologies, 2023)
Education is a process of interaction and communication among all participants, in which each of them has an impact on the outcome. Today, in the conditions of the modern world, cooperation between the teacher and the student acquires new forms and characteristics. The teacher is no longer just a source of knowledge but becomes a partner and helper for the student. The quality of communication between the student and the teacher depends on their readiness for dialogue and mutual understanding, absence of coercion and orders. A comprehensive approach to education and communication allows for a deep understanding of the processes and their improvement. Higher education institutions need to pay special attention to issues of strategic communication development, branding, and image. Clear and well-planned communication systems should be implemented at the level of structural units in order to achieve success. Providing adequate material and technical resources as well as information and communication technologies is crucial for effective use of various teaching methods and forms. However, communication between a teacher and a student should not only be about academic topics, but also about support, motivation, and personal development.